Performance Improvement of AlN Crystal Quality Grown on Patterned Si(111) Substrate for Deep UV-LED Applications - Tran, Binh Tinh (Sci Rep, 2016)
An AlN template layer is required for growth of AlGaN-based deep ultraviolet light-emitting diodes (UV-LEDs). However, the crystal quality of AlN templates grown on both flat and patterned Si substrates has so far been insufficient for replacing templates grown on sapphire substrates. In this work, we grew a high-quality AlN template on 2 in. micro-circle-patterned Si substrate (mPSiS) with two different sizes and shapes through controlling the bias power of inductively coupled plasma (ICP) etching. The experimental results showed that the best AlN template was obtained on a large pattern size with a bow-angle shape and the template had X-ray rocking curves with full widths at half-maximum of 620 and 1141 arcsec for the (002) and (102) reflection planes. The threading dislocation density near surface of AlN template through transmission electron microscopy (TEM) estimation was in the order of 10(7) cm(−2), which is the lowest dislocation density reported for a Si substrate to our knowledge. A strong single electroluminescence (EL) peak was also obtained for an AlGaN-based deep UV-LED grown on this template, means that it can be used for further developing high-efficiency deep UV-LEDs.